Geographic profiling - Rossmo, Kim (New York New York, 2025)
Geographic Profiling explores this cutting-edge investigative methodology for determining the most probable area of an offender's residence by analyzing the locations of a series of connected crimes. Geoprofiling allows police detectives and law enforcement officers to prioritize suspects, focus their investigations, and manage information overload. This extensive and exhaustive work explains the underlying theories and operational principles of the methodology.